2005
DOI: 10.1007/s11270-005-6273-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Available Cadmium in Relation to Soil Properties and Landuse in an Arid Region in Central Iran

Abstract: Due to potential problems associated with their toxicities, concentration of heavy metals in soils is of great environmental concern. To evaluate Cd content, its spatial pattern, and availability in the surface soils of agricultural, industrial and urban regions of Isfahan, central Iran, we collected 255 topsoil samples (0-20 cm) from the nodes of an irregular grid in a study area of 6800 km 2 . In the soil samples we measured total and DTPA-extractable Cd concentrations, soil pH, organic mater (OM), clay cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
2
22
1
6
Order By: Relevance
“…As the proportion of metals fractions is controlled by the soil properties (Naidu et al, 1994), correlation analysis was made to assess the soil properties controlling Cd fractionation in these soils. DTPA-extractable Cd Concentrations were positively correlated with soil electrical conductivity (r = 0.65, p< 0.01), it was reported before by Amini et al (2005).…”
Section: Single Extractionsupporting
confidence: 65%
“…As the proportion of metals fractions is controlled by the soil properties (Naidu et al, 1994), correlation analysis was made to assess the soil properties controlling Cd fractionation in these soils. DTPA-extractable Cd Concentrations were positively correlated with soil electrical conductivity (r = 0.65, p< 0.01), it was reported before by Amini et al (2005).…”
Section: Single Extractionsupporting
confidence: 65%
“…It is generally accepted that the pH of a soil is one of the most important factors controlling the uptake of heavy metals by plants (Amini et al, 2005). The increase in pH after P-application was due to ligand exchange reactions, where surface hydroxyl groups coordinated with a metal cation (e.g., Fe and Al) are replaced by phosphate ions (Bolan et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…RL with the highest percentage of clay maintains more available Cu on their adsorption exchange sites. Negative correlation between CaCO 3 and Cu may be originated from precipitation process and mostly Cu carbonate as Renella et al (2004) and Amini et al (2005) reported. Therefore, although there was no significant difference between total Cu in three land uses, it seems that different land uses resulted in significant differences in Cu DTPA forms through higher amounts of clay content and lower percentages of CaCO 3 .…”
Section: Dtpa-extractable Form Of Heavy Metalsmentioning
confidence: 88%
“…In addition, several researchers have also described the potential risks of heavy metals entering into human bodies through edible plants grown in contaminated soils (Bai et al 2010a;Dumat et al 2006;Notten et al 2005). Whereas total heavy metal concentrations and the concentrations of extractable heavy metals can be used to assess the level of contamination (Zhao et al 2012), the available soil metal concentrations predict metal transfer from soil to crops better than total metal concentrations (Amini et al 2005). Zhao et al (2012) showed that the areas with the highest human health risks do not directly coincide with the areas of highest heavy metal concentrations, but do coincide with the areas of lower soil pH.…”
Section: Introductionmentioning
confidence: 99%